Development of a core outcome domain set for clinical research on capillary malformations (the COSCAM project). (16th June 2021) - Langbroek, G.B.; Wolkerstorfer, A.; Horbach, S.E.R.; Spuls, P.I.; Kelly, K.M.; Robertson, S.J.; van Raath, M.I.; Al‐Niaimi, F.; Kono, T.; Boixeda, P.; Laubach, H.J.; Badawi, A.M.; et al.
Abstract: Background: Due to a large variety in treatment outcomes reported in therapeutic trials and lacking patient‐relevant outcomes, it is hard to adequately compare and improve current therapies for patients with capillary malformations (CMs). The Core Outcome Set for Capillary Malformations (COSCAM) project aims to develop a core outcome set (COS) for use in future CM trials, in which we will first develop a core outcome (sub)domain set (CDS). Here, we describe the methods for the development of a CDS and present the results of the first development stage. Methods: The COSCAM project is carried out according to the recommendations of the Cochrane Skin Core OUtcomes Set INitiative (CS‐COUSIN) and the Core Outcome Measures in Effectiveness Trials (COMET) initiative. During the first stage, we identified all potentially relevant outcome subdomains based on a systematic review, two focus group sessions and input from patient representatives of Dutch patient organizations and the COSCAM‐founding group. In stage two, we will present the subdomains in a three‐round e‐Delphi study and online consensus meeting, in which CM patients, parents/caregivers and CM experts worldwide rate the importance of the proposed subdomains, hereby finalizing the core outcome (sub)domains of the CDS. Results: A total of 67 potential outcome subdomains were included; sixteen were previously used in the literature, 20 were proposed by Dutch patients and their parents/caregivers ( n = 13) in focus group sessions and 38 were suggested by the experts of the COSCAM‐founding group. Seven were excluded because of overlap. Conclusion: The final CDS may serve as a minimum standard in future CM trials, thereby facilitating adequate comparison of treatment outcomes. After this CDS development, we will select appropriate outcome measurement instruments to measure the core outcome subdomains.